Ija Sunatana&Dede Kania: SISTEM HUKUM GANTI RUGI DALAM HUKUM PIDANA ISLAM SEBAGAI BAHAN PEMBAHARUAN HUKUM PIDANA INDONESIA - Ija Suntana Dede Kania (Universitas Islam Negeri Mataram, 2018)
Abstract: This research reveals that the settlement of criminal cases in Indonesia is at present constructed through criminal justice system organized by the government. The system places abuse of criminal law as an abuse of state concerns, not as a violation to individuals. The formulation and meaning of criminal acts are not viewed as acts of personally and concretely violating the victim’s law concern, but they are seen as the abuse of state norms. Meanwhile, from the model of criminal case settlement in Islamic criminal law, it is found that the arrangement differs from the Indonesian current state of the art. The flow of formal Islamic criminal law provides an opportunity for the victim to prosecute, even to determine the compensation amount. Academically, the formulation of Islamic criminal law possesses a potential of being a reforming model for the setllement of criminal cases in Indonesia.